Correction to: Tissue-Scale Biomechanical Testing of Brain Tissue for the Calibration of Nonlinear Material Models (Current Protocols, (2022), 2, 4, 10.1002/cpz1.381) - Faber, Jessica; Hinrichsen, Jan; Greiner, Alexander; Reiter, Nina; Budday, Silvia (Current Protocols, 2022)
Current Protocols is issuing corrections for the following Protocol article. Faber, J., Hinrichsen, J., Reiter, N., & Budday, S. (2022). Tissue-scale biomechanical testing of brain tissue for the calibration of nonlinear material models. Current Protocols, 2, e381. doi: 10.1002/cpz1.381. In the above-referenced article: Equation 28 was corrected. Two instances of superscript T were changed to superscript −t. Figure 11 was replaced with an updated version. The current version online now includes these corrections and may be considered the authoritative version of record.
CRIS-Team Scopus Importer:2022-08-05